2021
DOI: 10.1021/acs.nanolett.1c01734
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Charge-Transfer-Induced Strong Optical Emission from Herringbone H-Aggregates

Abstract: Luminescence in molecular aggregates can be quenched either by intermolecular charge transfer or by forming a dipole-forbidden lower Frenkel exciton in H-aggregate. Taking intermolecular charge transfer and excitonic coupling into a three-state model through localized diabatization, we demonstrate that the low-lying intermolecular charge-transfer state could couple with the upper bright Frenkel exciton to form dipole-allowed S1 that lies below the dark state, which accounts for the recent experimentally discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…This feature probably indicates that the self‐assembled nanorods effectively enhances the order of H‐aggregation behavior. [ 22 ] Further, the PLQY of DDC 3 F‐based nanorod film is measured as 87%, which is slightly lower than that in dilute solution (PLQY = 97%) but can be 1.5 times higher than that on amorphous film (57%) without crystalline morphologies (Figure 2b). Thus, such crystalline nanorod film enables to suppress general aggregation‐caused quenching effect and maintain the high efficient deep‐blue emission, seemingly analogous to the presence of CIEE feature.…”
Section: Resultsmentioning
confidence: 98%
“…This feature probably indicates that the self‐assembled nanorods effectively enhances the order of H‐aggregation behavior. [ 22 ] Further, the PLQY of DDC 3 F‐based nanorod film is measured as 87%, which is slightly lower than that in dilute solution (PLQY = 97%) but can be 1.5 times higher than that on amorphous film (57%) without crystalline morphologies (Figure 2b). Thus, such crystalline nanorod film enables to suppress general aggregation‐caused quenching effect and maintain the high efficient deep‐blue emission, seemingly analogous to the presence of CIEE feature.…”
Section: Resultsmentioning
confidence: 98%
“…This also demonstrated that the coordination-induced approach can greatly enhance the charge separation of the D−π–A chromophore and enhance the intermolecular charge transfer delayed emission. As a whole, the RTP behaviors originate from well-separated and aggregation-generated triplet emission. , …”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be mentioned that although the method we employed has achieved satisfactory results in mechanism explanation and property prediction, quantitative modulation of the luminescent behaviors of organic materials is still challenging. 32,[47][48][49][50]…”
Section: Discussionmentioning
confidence: 99%